2019
DOI: 10.1158/1055-9965.epi-18-0169
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Novel Histoplasmosis Enzyme Immunoassay to Evaluate Suspicious Lung Nodules

Abstract: Background: Granulomas caused by infectious lung diseases present as indeterminate pulmonary nodules (IPNs) on radiography. Newly available serum enzyme immunoassay (EIA) for histoplasmosis has not been studied for the evaluation of IPNs. We investigated serum biomarkers of histoplasmosis antibodies as an indication of benign disease in IPNs from a highly endemic region. Methods: A total of 152 serum samples from patients presenting with pulmonary nodules 30 mm in maximum diameter were analyzed for histoplasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…As this variability exists, a test or tool that would lend additional information about subject risk could be beneficial to increasing standardization of care between providers. Recently, a minimally invasive biomarker using serum enzyme immunoassay analysis has been developed to address this problem (sensitivity 42%, specificity 85%) (26). A radiomic approach is potentially advantageous as it utilizes existing data -requiring no additional sample collection or work-up process.…”
Section: Discussionmentioning
confidence: 99%
“…As this variability exists, a test or tool that would lend additional information about subject risk could be beneficial to increasing standardization of care between providers. Recently, a minimally invasive biomarker using serum enzyme immunoassay analysis has been developed to address this problem (sensitivity 42%, specificity 85%) (26). A radiomic approach is potentially advantageous as it utilizes existing data -requiring no additional sample collection or work-up process.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant was tested for histoplasmosis by MiraVista's proprietary EIA for IgG and IgM antibodies, the methodology of which has been reported elsewhere. 8,10 The EIA results were standardized to enzyme immunoassay antibody units (EU), with values of 10 EU or greater indicating a positive test consistent with active disease. These cutoffs were determined based on the manufacturer's recommendation.…”
Section: Serologic Testingmentioning
confidence: 99%
“…All patients with both positive IgG and IgM antibodies (n ¼ 8) had benign disease (positive predictive value 100%) consistent with granuloma. 8 Our previously published pilot study demonstrated that integrating a novel fungal biomarker into the evaluation of IPN for lung cancer could be useful in areas of endemic fungal disease. The aims of the study reported here were to validate the use of Histoplasma IgG and IgM as measured by EIA in the diagnosis of benign IPN across populations with different local histoplasmosis exposure levels and different prevalences of lung cancer.…”
mentioning
confidence: 99%
“…In fact, virtually the entire population in some highly endemic areas may be repeatedly exposed (Goodwin et al, 1981). Pulmonary nodules are a common incidental finding on medical imaging of patients living in endemic areas; in highly endemic areas, up to 12% of these nodules may be associated with infection with H. capsulatum (Benedict et al, 2019;Deppen et al, 2019). Such latent infections are usually asymptomatic, although they may present as invasive disease decades later upon immunosuppression (Bourgeois et al, 2011).…”
Section: Histoplasmosismentioning
confidence: 99%